Pengaruh Store Atmosphere dan Lokasi terhadap Minat Beli Konsumen Pada Goto Living Store Curug - Asmin; Yunus, Muhammad (Soratekno Publisher, 2026)
This study aims to determine the effect of store atmosphere and location on consumer purchase intention at Goto Living Store Curug. The research variables consist of store atmosphere (X1), location (X2), and consumer purchase intention (Y). The method used is probability sampling, which is a sampling technique that provides equal opportunities for each element (member) of the population to be selected as part of the sample. The specific technique applied is simple random sampling, in which sample members are selected randomly from the population without considering existing strata. Each element of the population has an equal chance of being chosen as a sample. The data analysis includes descriptive statistical tests, validity tests, reliability tests, classical assumption tests, correlation analysis, coefficient of determination, regression analysis, and hypothesis testing (t-test and F-test) using IBM SPSS version 26.0. The results indicate that, simultaneously, store atmosphere and location have a significant and positive effect on consumer purchase intention at Goto Living Store Curug. Partially, store atmosphere has a significant and positive effect on consumer purchase intention at Goto Living Store Curug, and location also has a significant and positive effect on consumer purchase intention at Goto Living Store Curug.